Aesthetic style transferring method based on deep neural network between Chinese landscape painting and classical private garden's virtual scenario. Issue 1 (31st December 2023) - Hong, Shuai; Shen, Jie; Lü, Guonian; Liu, Xiaoyan; Mao, Yirui; Sun, Nina; Tang, Long
ABSTRACT: Most of the existing virtual scenarios built for the digital protection of Chinese classical private gardens are too modern in expression style to show the aesthetic significance of their historical period. Considering the aesthetic commonality between traditional Chinese landscape paintings and classical private gardens and referring to image style transfer, here, a deep neural network was proposed to transfer the aesthetic style from landscape paintings to the virtual scenario of classical private gardens. The network consisted of two parts: style prediction and style transfer. The style prediction network was used to obtain style representation from style paintings, and the style transfer network was used to transfer style representation to the content scenario. The pre-trained network was then embedded into the scenario rendering pipeline and combined with the screen post-processing method to realise the stylised expression of the virtual scenario. To verify the feasibility of this methodology, a virtual scenario of the Humble Administrator's Garden was used as the content scenario and five garden landscape paintings from different time periods and painting styles were selected for the case study. The results demonstrated that this methodology could effectively achieve the aesthetic style transfer of a virtual scenario.